TeamMates: A Model to Support Mentoring in Rural Schools - Leon Dappen; Jody C. Isernhangen (Journal of Research in Rural Education, 2002)
Mentoring Relationships have proven to provide benefit to youth and are expanding rapidly into schools. There was concern wether or not the economic and demographic issues of rural communities and schools would limit success of mentoring programs in rural schools. This study focuses on TeamMates, a state-wide, school-based, one-to-one, adult-to-youth mentoring program which includes extensive support for program implementation and ongoing operation. The program was effective in rural schools in demonstrating positive perceptions of change in students' behavior as reported by students, parents, teachers, and mentors. Rural and nonrural groups' perceptions of change were at least average and above. Rural and nonrural groups percieved the program in a similar manner. Rural communities and schools were able to provide mentors and staff to support program implementation at a rate that surpassed non rural schools. Needs for future research and resources for information for rural administrator considering implementing a student mentoring program are shared.